Beach Chair Versus Lateral Decubitus Surgical Positioning for Arthroscopic Anterior Shoulder Stabilization: A Retrospective Comparison of Clinical and Patient-Reported Outcomes. Issue 6 (28th June 2022) - Paul, Ryan W.; Streicher, Sydney; Osman, Alim; Ukekwe, Chuka; Zareef, Usman; Freedman, Kevin B.; Erickson, Brandon J.; Hammoud, Sommer; Bishop, Meghan E.
Background: Surgical positioning can affect both perioperative and postoperative complication rates. It is unclear whether beach-chair versus lateral decubitus positioning affects outcomes in patients undergoing arthroscopic anterior shoulder stabilization surgery. Purpose: The purpose of this study was to compare recurrent instability, complications, and patient-reported outcomes between patients who underwent arthroscopic anterior shoulder stabilization in the beach-chair versus the lateral decubitus positions. It was hypothesized that recurrent instability, complications, and patient-reported outcomes would not be affected by surgical positioning. Study Design: Cohort study; Level of evidence, 3. Methods: The authors reviewed the medical records of patients who underwent shoulder stabilization ( Current Procedural Terminology codes 29806 and 29807) from 2015 to 2019. Patients were included only if anterior instability was confirmed, arthroscopic surgery was performed in response to shoulder instability, and a minimum of 2 years of follow-up data were available. Data collected for eligible patients included perioperative and postoperative complications, recurrent instability, reoperation, and revision. Patients also completed surveys for the American Shoulder and Elbow Surgeons (ASES) score, Single Assessment Numeric Evaluation (SANE) score, Oxford Shoulder Instability (OSI) score, and a return to any level of sport (RTS) questionnaire. Results: Overall, 294 patients (162 lateral decubitus and 132 beach-chair positions) were included, with an average follow-up of 2.4 ± 1.6 years. There were no significant differences in demographics between groups, nor were there differences in the rates of postoperative dislocations, subjective instability, reoperations, revisions, or complications. There was a trend toward a higher revision rate in the beach-chair group (beach-chair, 6.1% vs lateral decubitus, 1.9%; P = .069). There was no significant difference between groups regarding RTS rates or postoperative ASES, SANE, and OSI scores at 3.3 ± 1.1 years postoperatively. Conclusion: Surgical positioning for arthroscopic anterior shoulder stabilization did not significantly affect recurrent instability, complications, and patient-reported outcomes. Both beach-chair and lateral decubitus positioning provided good outcomes for anterior shoulder stabilization, with an overall recurrent dislocation rate of 7.8% at a mean of 3.3 years after surgery.